Anaerobic Digestion of Feedstock Grown on Marginal Land: Break-Even Electricity Prices - Yakubu Abdul-Salam; Melf-Hinrich Ehlers; Jelte Harnmeijer (Energies, 2017)
Marginal farm land is land characterised by low food, feed and fodder crop productivity due to soil and environmental limitations. Such land may however be utilised for bio-energy crop production. We investigate the economic viability of small scale combined heat and power anaerobic digestion (CHP AD) projects based on feedstock from farm waste and bio-energy crops grown on a representative temperate latitude marginal farm land in the UK. Using a realistic set of five project feedstock-mix scenarios, and considering standard technology and current market and policy regimes, we deploy a stochastic framework to assess prices of electricity required for these projects to break-even and conduct sensitivity analyses of key project parameters. Accounting for the current market prices and policy tariffs for heat, we find that critical electricity sale prices of about 17.46 p/kWh to 27.12 p/kWh are needed for the projects to break even. These prices are well above the current combined feed-in-tariff support and market prices for electricity over the past years in the UK. We conclude that the use of marginal land to generate power for export using small-scale CHP AD in the UK and the wider temperate latitude countries is unviable, if energy and farming policy regimes do not provide substantial support.